Testing and Comparison of SN754410N and L293D Driver IC Variants - Phoa, Victor; Rakhmad, Hariyono (Jurnal Arus Elektro Indonesia, 2024)
The popular transistor-based driver L293D has been produced by several different manufacturers and some have increased functions such as the SN754410N IC. However, replacing driver ICs from the same or different manufacturers sometimes found compatibility problems such as driver unresponsiveness in controlling the motor. To find out the scientific reasons that cause this problem, this study tested the current-carrying ability and switching delay for ICs from ST, HLF, and SN754410N fabrications. From the test results, it was found that there were differences in the ability to conduct current, and differences in the duration of the switching delay, and it was also found that the IC was damaged as much as 10 percent of the samples from the ST fabrication.